The Influence of Parent-Child Communication Frequency on the Self-Confidence Levels of Out-of-Town Students at the Faculty of Social Sciences and Law, Jakarta State University (FISH UNJ) - Firdaus, Aura Safina (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to evaluate the extent to which interactions between parents and out-of-town students at the Faculty of Social Sciences and Law, Jakarta State University (FISH UNJ), influence their self-confidence in navigating academic and social life. Regular and high-quality communication between out-of-town students and their parents is believed to positively contribute to the students' emotional stability and confidence in facing various challenges away from home. Utilizing a quantitative approach through surveys, this research employs structured questionnaires to measure two primary variables: the frequency of communication with parents and the self-confidence levels of students. Data analysis is conducted using simple linear regression analysis to identify the causal relationship between these variables. The findings of this study are expected to provide both theoretical and practical insights into the significance of family communication in supporting the psychological development of out-of-town students.Â